POLA KEJADIAN BBLR: KORELASI ASPEK DEMOGRAFI DAN EKONOMI KELUARGA - Inayati, Inna Noor; S, Kartini; Auliah, Rezki; Muhtaruddin, Erwin (Ensiklopedia of Journal, 2024)
Abstract: The incidence of low birth weight (LBW) is one of the most important health problems in the world. Nationally, LBW is still a significant problem and affects maternal and child health in various regions. Based on a preliminary survey conducted at RSUD Melawi, there were 6 LBW babies out of 10 mothers who gave birth which was related to the age of the mother. Based on the income aspect, there were 4 low-income mothers and 2 high-income mothers. The purpose of the study was to determine the correlation of demographic and economic aspects of the family with the incidence of Low Birth Weight Infants (LBW). The research design used in this study was case control. The study was conducted in January 2024 at the Melawi Regional General Hospital. The population was pregnant women who gave birth at the Melawi Regional General Hospital during January to December 2023 as many as 248 people. The sample amounted to 35 case respondents and 35 control respondents selected using accidental sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between maternal age (p value: 0.001) and no relationship between family economy (p value: 0.623) with the incidence of Low Birth Weight Infants (LBW). It is recommended for the hospital to improve the ability to handle pregnant women at risk so as to help smooth the delivery and for pregnant women to routinely visit to check their pregnancy in order to know how the development of the fetus in the womb.Keywords: Low Birth Weight Infants, Demographic Aspects, Family Economics.